Feedback from L1 users – a potential facilitator of L2 use. Issue 5 (27th May 2020) - Marton, Enikő; MacIntyre, Peter D.
ABSTRACT: In bilingual settings, the communication between majority and minority language speakers usually takes place in the majority language. This paper examines whether majority language speakers, who receive positive feedback from minority language speakers when accommodating to them, use the minority language more frequently for authentic purposes. We propose positive feedback from L1 users as a potential facilitator of L2 use. We report the development and the properties of the scale we utilised to assess L1 user feedback (L1FB). We embedded L1FB into the socio-contextual model of L2 communication and tested four hypotheses regarding the effect of L1FB on L2 use among majority language speaking high school students in bilingual Finland. All the hypotheses were supported by the data. Most importantly, L1FB significantly moderated the effect of L2 confidence on L2 use. L2 confidence had a larger effect on L2 use among those who received positive feedback. In the absence of positive L1FB, however, confident L2 learners used their L2 as little as their more anxious and less competent peers did. We discuss the relevance of L1FB with regard to authentic L2 use in general and the promotion of lesser used languages, in particular.